CNG for Commercialization of Small Volumes of Associated Gas - Tractebel Engineering (World Bank, Washington, DC, 2017)
The Global Gas Flaring Reduction Partnership (GGFR) provides its members with overviews of the potential solutions to recover and monetize the flared and/or associated gas. This study analyses two options that could be used for this monetization of small volumes (1 -15 MMscf/d): the LNG and CNG chain concepts. Technologies are available for both concepts, with different maturity level from the gained experiences and for different transportation conditions (quantities, distances). The available technologies allow a choice of implementation options to suit the volume of gas to be transported and the distance from field to consumer. The cost of the chain depends upon the parameters governing the gas recovery, its transportation and its delivery. Among these parameters the most important are the gas volume and the transportation distance.